Epilogue—Turning to the Wall: Concepts across Space and Time - Tóth, György (Review of International American Studies, 2018)
György Tóth University of Stirling Scotland, United Kingdom Epilogue—Turning to the Wall: Concepts across Space and Time Abstract: The epilogue to this journal issue interrogates a variety of aspects of walls as mental structures and tropes of historical memory. Engaging with the issue’s contributing authors, Tóth argues that the idea of the wall functions as metonymy, activating a siege mentality and mobilizing its target audience – hence its rhetorical power and attraction as policy. Discussing the wall’s symbology as a border of the nation state but also pointing out its increasing privatization, the piece concludes with an exploration of the potential that walls may have for the creative subversion of their original function to seal off, categorize and divide humans. Keywords: commentary, Trump, historical memory, metonymy, art